Managing university data for quality: from the lens of a practitioner / Roziah Mohd Janor - Mohd Janor, Roziah
Data should be a true representation of what it is intended to reflect. With data, we derive information. And information, when you have it, translates into power. Yet, nobody can claim to know everything. Or rather, it may be more accurate to say that it is impossible to know everything. Decisions are made based on the information that a person has at a particular time, which may sometimes be considered the best decision that can be made with the information available. However, on the other side of the spectrum, one can also be made not to know. Whether intentional or not, misrepresentations of data may also lead to decisions where, if a person has a more accurate understanding of what the data means, that decision might have been different. After spending more than thirty years working with data, as the Vice-Chancellor of Universiti Teknologi MARA (UiTM), I am now in the position where I can access a wealth of data, and thus a lot of information. However, being in this position has also made me question many things. I look back to records of old and wonder, why were certain decisions made in the past? To me, it is simple mathematics, simple calculation. There is always an exchange of value for returns, but some decisions of the past that were made for this university do not fit this equation. Why?